Nouns in Balinese - Ni Putu Parmini; Desak Nyoman Alit Sudiarthi; I Wayan Mawa; Temaja, I Gede Bagus Wisnu Bayu (International Journal of Education, Vocational and Social Science, 2024)
This study aimed to identify nouns in the Balinese language. This study aims to analyze the morphological form of nouns, their syntactical features, and their semantic roles. The data were collected from Balinese speakers, libraries, and researchers who are native Balinese speakers. The data were analyzed using the distributional and referential identity methods. The results showed that Balinese nouns have monomorphic and polymorphic forms. In its syntactic features, nouns may join demonstratives, numerals, and adjectives and may be omitted with the word ‘no.’ In its semantic roles, nouns can mean the perpetrator, the patient, the receiver, the means, the time, and the known.